“La Vestimenta Indígena en la Identidad Cultural en las niñas de segundo año de Educación Básica del paralelo “A” de la Escuela Rosa Zárate, Parroquia Licto, Cantón Riobamba, Provincia de Chimborazo período 2015-2016” - Alcocer Naula, Elvia Verónica (2016)
This research is titled “The Indigenous Dress In The Cultural identity Of First Year Elementary School Student In Parallel “A” At Rosa Zarate School, Licto Parish, Riobamba Canton, Province of Chimborazo for the period of 2015-2016”. This institution and the entire educational system, should aim to inculcate indigenous attire as a fundamental pillar for the preservation of their cultural identity. Unfortunately, students are no longer dress in the traditional indigenous clothing, without regard to the cultural identity being sacrificed by changing this tradition. This work was based on a bibliography updated to carry out the operationalization of the independent and dependent variables in order to achieve the proposed objectives. It was based on a non-experimental, documentary, field, applied and exploratory research to deepen the research. A survey was given to the first year elementary school teacher and an observation sheet was used to assess the girls at Rosa Zarate School. Each aspect of the research had its respective evaluation and interpretation through tables and graphs. After a thorough analysis, the conclusions and recommendations were present: this has a large impact on the social, education and family context of our culture. The history and customs that are represented through the use of the traditional clothing by indigenous people are treasured values for our country. They are an important aspect that help provide understanding of the importance and richness that indigenous traditional clothing represents. It also helps advance the respect for their traditions, customs, clothing which should engross the educational system the need to respect, cultivate and promote cultural diversity in schools.